2023
DOI: 10.3390/bioengineering10101228
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Acute Myeloid Leukemia: A Literature Review of Emerging Strategies

Luca Guarnera,
Carlos Bravo-Perez,
Valeria Visconte

Abstract: In the last twenty years, we have witnessed a paradigm shift in the treatment and prognosis of acute myeloid leukemia (AML), thanks to the introduction of new efficient drugs or approaches to refine old therapies, such as Gemtuzumab Ozogamicin, CPX 3-5-1, hypomethylating agents, and Venetoclax, the optimization of conditioning regimens in allogeneic hematopoietic stem cell transplantation and the improvement of supportive care. However, the long-term survival of non-M3 and non-core binding factor-AML is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 152 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…We explored the correlation of CSRP1 with immune checkpoint genes and observed associations with eight immune checkpoint genes (TNFSF18: R = 0.30, CD244: R = − 0.30, CD40: R = 0.38, TNFRSF8: R = 0.36, CD80: R = 0.27, CD200R1: R = 0.35, CD276: R = 0.43, LAG3: R = 0.27). Described in a study, the CTLA4/CD80-86 Pathway, CD200/CD200R, LAG3, and CD276 have been identified or tested as promising targets in AML [ 34 ]. The alterations in these CSRP1-related genes may form a complex network affecting the immune response in AML patients at the genetic level, contributing to differential sensitivity to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the correlation of CSRP1 with immune checkpoint genes and observed associations with eight immune checkpoint genes (TNFSF18: R = 0.30, CD244: R = − 0.30, CD40: R = 0.38, TNFRSF8: R = 0.36, CD80: R = 0.27, CD200R1: R = 0.35, CD276: R = 0.43, LAG3: R = 0.27). Described in a study, the CTLA4/CD80-86 Pathway, CD200/CD200R, LAG3, and CD276 have been identified or tested as promising targets in AML [ 34 ]. The alterations in these CSRP1-related genes may form a complex network affecting the immune response in AML patients at the genetic level, contributing to differential sensitivity to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The management of t-MN and, in particular, TP53-mutated MN is still an unmet medical need. Nevertheless, the growing number of possible therapeutic targets [124], alongside the broader accessibility to HSCT, hold the promise of significant improvements in the near future. In particular, considering the overlapping mutational features between de novo and t-MN and the profound difference in the leukemic niche and in the staminal senescent mechanisms, the latter mechanism could be a promising target for senolytic agents which, alone or combined with chemotherapy, showed high efficacy in preclinical models [64,125].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%